Ceria-samarium binary metal oxides: A comparative approach towards structural properties and soot oxidation activity - Anantharaman, Anjana P.; Geethu, J.; Rishab, Mohammed P.; Dasari, Hari Prasad; Lee, Jong-Ho; Dasari, Harshini; Babu, G. Uday Bhaskar (ELSEVIER SCIENCE BV, 2018)
Binary metal oxides of CeO2-Sm2O3 (CSx, x varies from 10 to 90 mol%) along with pure CeO2 and Sm2O3 were synthesised successfully by the EDTA-Citrate method. From XRD, Raman spectroscopy and UV-vis DRS results, the whole composition of metal oxides exist in three phases: (fluorite phase (F) (CS10-CS30), bi-phase (fluorite (F) + cubic (C)) (CS30-CS90) and cubic phase (C) (Sm2O3)). For CSx samples, the calculated band gap energy values obtained from the UV-vis DRS results were in between 3.0-5.1 eV and fluorite phase samples (CS10-CS30) displayed lower band gap energy values (3.04-3.07 eV) than compared to the samples in other phases. Similarly, from XPS analysis, fluorite phase samples (CS10-CS30) showed higher surface oxygen vacancy concentration than compared to samples in other phases. Catalytic activity for soot oxidation is carried out on CSx samples, and the T-50 temperature is in between 480-540 degrees C. Fluorite phase samples (CS10-CS30) showed higher surface area, lower degree of agglomeration, lower band gap energy, higher oxygen vacancy concentration and better catalytic activity for soot oxidation. Among all the CSx samples, CS10 sample displayed highest surface area (38 m(2)/g), lowest degree of agglomeration (0.36), lowest band gap energy (3.04 eV), highest oxygen vacancy concentration (64%) and highest soot oxidation activity (T50 = 480 degrees C). The order of the soot oxidation activity of CSx samples followed the same trend of band gap energy values.
Keywords: GD-DOPED CERIA; CATALYTIC-ACTIVITY; BAND-GAP; OPTICAL-PROPERTIES; CO OXIDATION; OXYGEN; CEO2; TEMPERATURE; POWDERS; O-2